Wednesday
March 29, 2017

Post a New Question

Posted by on .

I have to factor the expression and use fundamental identities:

sins^2xcscx^2-sin^2x

sec^4x-tan^4x

  • trig - ,

    sins^2xcscx^2-sin^2x
    = sin^2x(csc^2x - 1)
    = sin^2x(cot^2x)
    = sin^2x(cos^2x/sin^2x)
    = cos^2x

    sec^4x - tan^4x
    = (sec^2x - tan^2x)(sec^2x + tan^2x)
    = (tan^2x + 1 - tan^2x)(tan^2x + 1 + tan^2x)
    = 1(2tan^2x +1)
    = 2tan^2x + 1

  • trig - ,

    OHHH okay, THANKS!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question